Lewis Harcourt’s journal of the 1914 war crisis - Young, John W. (Taylor & Francis, 2017)
Lewis Harcourt, who was Colonial Secretary in Britain's Liberal government, from 1908 to 1915, kept a political journal for many years, some earlier parts of which have already been published. Reproduced below is the whole neat version of the journal from 26 July 1914, when Harcourt first mentions the events of the ‘July Crisis’, until 4 August, when Britain declared war on Germany. Originals of the entries are kept at the Bodleian Library, Oxford in file Ms. Eng. c. 8269 of the ‘Further Papers of Lewis Harcourt’, which only came to light in 2008. Historians can be grateful that Harcourt kept such a record of ministerial discussions during the July Crisis, because no official records were taken of Cabinet meetings before 1916, apart from short reports by the Prime Minister to the King. There are some diary entries, letters and memoranda from those involved, but the only source with comparative detail to Harcourt's is the diary kept by the education minister, Jack Pease, which has already been published.